2018
DOI: 10.1002/ece3.4017
|View full text |Cite
|
Sign up to set email alerts
|

Roads to isolation: Similar genomic history patterns in two species of freshwater crabs with contrasting environmental tolerances and range sizes

Abstract: Freshwater species often show high levels of endemism and risk of extinction owing to their limited dispersal abilities. This is exemplified by the stenotopic freshwater crab, Johora singaporensis which is one of the world's 100 most threatened species, and currently inhabits less than 0.01 km2 of five low order hill streams within the highly urbanized island city‐state of Singapore. We compared populations of J. singaporensis with that of the non‐threatened, widespread, abundant, and eurytopic freshwater crab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 84 publications
1
1
0
Order By: Relevance
“…data). Our uncorrected ‘p’ sequence divergence value is within the range that has been reported intraspecifically for freshwater crabs, whereas the haplotypic and nucleotide diversity reported for P. lividus was moderately higher compared with that reported for COI in freshwater crabs (Tay et al, 2018).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…data). Our uncorrected ‘p’ sequence divergence value is within the range that has been reported intraspecifically for freshwater crabs, whereas the haplotypic and nucleotide diversity reported for P. lividus was moderately higher compared with that reported for COI in freshwater crabs (Tay et al, 2018).…”
Section: Discussionsupporting
confidence: 75%
“…Although mitochondrial DNA (mtDNA) markers, such as cytochrome c oxidase subunit I (COI) and 16S rRNA, have been used extensively in phylogeographical studies of invertebrates, including freshwater crabs (Daniels, 2011;Daniels et al, 2006;Daniels & Klaus, 2018;Daniels et al, 2002;Gouws et al, 2015;Phiri & Daniels, 2016;Tay et al, 2018), microsatellites, such as nuclear DNA (nDNA) markers, have not been used to examine the population structure of an Afrotropical freshwater crab species. Several studies have demonstrated that phylogeographical studies can often be complemented by ecological niche modelling to understand the relationships between lineage distribution and niche divergence (Hofmeyr et al, 2020).…”
Section: Introductionmentioning
confidence: 99%